Aplicación de calceína para la estimación del crecimiento de la almeja amarilla Mesodesma mactroides Reeve, 1854 - Mauro L. Lepore (Revista de Biología Marina y Oceanografía, 2009)
Growth rates of Mesodesma mactroides were estimated comparing two different methods at the intertidal of the exposed sandy beach Santa Teresita, Argentina. Results of a short tagging-recapture experiment using the in situ fluorescent marking (MFI) method and subsequent size-increment analysis were compared with results from length-frequency distributions (DFT) analysis from a 25 month quantitative sampling. Residuals, derived from MFI method and DFT analysis, were of similar magnitude and distribution, suggesting that both methods are equally appropriate to estimate growth of M. mactroides. Calcein was useful as non-lethal growth marker for M. mactroides, emitting a bright green fluorescence band under blue light.